Prototype Alat Pengontrol Pergerakan Tripod Berbasis Mikrokontroler - Indah Monisa; Ade Zulkarnain Hasibuan; Rachmat Aulia; Munjiat Setiani Asih (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
This study aims to design a microcontroller-based tripod movement controller. Lots of people carry a camera when they are traveling or traveling. They brought cameras to make documentation while traveling for collection. While traveling, sometimes many travelers who travel alone or solo travelers have difficulty when they want to take pictures of themselves. Usually we will ask for help from other people who are around the place to take pictures so that the photos we take are good. If you are in a crowded place, of course this will not be a problem. However, if you are really alone, of course it will be difficult to do that. To overcome this, usually people use a tripod so he can take pictures of himself. The author tries to provide a solution to the problems that have been detailed previously by creating a system that can help photographers take pictures more easily. The system that will be made in the design of this microcontroller-based tripod movement controller uses bluetooth as a source of communication between the two Bluetooth pieces in building the system. wireless and to adjust the movement of the tripod in the specified direction using a servo motor, remote control as a remote controller, By connecting Arduino nano with bluetooth and a servo motor, the tripod can be moved remotely via the remote control. The purpose of this research is to develop a tool as an alternative that makes it easier for photographers to take pictures with a steady position. Keywords: Tripod, Bluetooth, Motor Servo, Remote Control, Arduino Nano